SERA FROM NIGERIAN CHILDREN WITH GENITOURINARY SCHISTOSOMIASIS HAVING IMMUNE COMPLEXES AND HEAT LABILE LEUCOCYTE MIGRATION INHIBI- TORY FACTORS WITHOUT IMPAIRED CELLULAR IMMUNITY (Biological Sciences - PJSIR, 2004)
There was a significant increase in the rate of synthesis of both albumin and globulin as a result of good adaptive mechanism which prevent hypoproteinemia in children with genitourinary schistosomiasis from endemic areas in Edo and Delta States, South Eastern Nigeria. Single radial immunodiffusion method and the Mantoux test were used to evaluate serum acute phase proteins and delayed hypersensitivity skin assay. While the Nytrel filter method of World Health Organization was employed in the counting of Schistosoma haematobium ova and the serum inhibitory factor to leucocyte migration was determined in accordance with WHO specifications with modifications in the preparation of the two antigens and a mitogen - BCG, IMV and PPD. Results were interpreted statistically using spearman’s coeffi- cient of correlation and regression analysis. Complement factors present in circulating soluble immune complex and complement dependant cell mediated and killed schistosomula. C4 decreased with increase in number of S.haematobium eggs while C3 (C3C) products increased with severity of infection. There was an acute phase response to tissue damage by all stages of schistosomes and inflammatory response of immune competent cells against schistosome antigens from eggs and worm organs, which resulted to increase in transferrin. It was suggested that the heat labile leucocyte migration inhibitory factors were present in the sera of S.haematobium infected children, and there was a reduced negative skin response to tuberculin antigen in the infected children. These facts establish the possession of adequate functioning ofthe cytotoxic CD8+ T lymplocytes in the infected children. The heat labile migration inhibitory factors are products ofimmune complexes which when activated by complements result to patechial haemorrhagic manifestations. Leucope- nia, atypical lymphocytes and plasma cells were observed in the blood which are characteristics of children who have experienced previous attack of S. haematobium infection.